Multicenter Clinicopathological Study of High-Grade Serous Carcinoma Presenting as Primary Peritoneal Carcinoma. Issue 4 (1st May 2018) - Komiyama, Shinichi; Nishijima, Yoshihiro; Kondo, Haruhiro; Nomura, Hiroyuki; Yamaguchi, Satoshi; Futagami, Masayuki; Arai, Hiroharu; Yokoyama, Yoshihito; Suzuki, Nao; Mikami, Mikio; Kubushiro, Kaneyuki; Aoki, Daisuke; et al.
Abstract : Objective: We conducted a multicenter clinicopathological study to characterize patients with high-grade serous carcinoma presenting as primary peritoneal carcinoma (clinical PPC). Methods: At 9 sites in Japan, patients with clinical PPC diagnosed according to Gynecologic Oncology Group criteria were enrolled retrospectively. The Gynecologic Oncology Group criteria allow for minor ovarian involvement by high-grade serous carcinoma. There was no systematic detailed histopathological review of the fallopian tubes to determine whether they were involved by serous carcinoma. Results: There were 139 patients and 64% were aged 60 years or older. Median pretreatment serum CA-125 was 1653.5 IU/mL. Pretreatment performance status was poor in more than 50%, endometrial cytology was positive in 40.3%, and the preoperative clinical diagnosis was correct in 72.7%. Primary debulking surgery was performed in 36% of patients, whereas 64% underwent neoadjuvant chemotherapy (NAC) with interval debulking surgery (IDS). The main tumor sites were the upper abdomen (greater omentum), extrapelvic peritoneum, mesentery, and diaphragm. Lymph node metastasis was found in 46.8% of patients undergoing systematic retroperitoneal node dissection. The optimal surgery rate was 32.0% with primary debulking surgery versus 53.9% with NAC and IDS ( P = 0.0139). The response rate was 82.0% with NAC and 80.6% with postoperative chemotherapy. Median progression-free survival was 19.0 months and median overall survival was 41.0 months. Multivariate analysis showed that prognostic factors for progression-free survival were NAC and residual tumor diameter after debulking surgery, whereas the only prognostic factor for overall survival was the residual tumor diameter. Conclusions: This study identified various characteristics of clinical PPC. Neoadjuvant chemotherapy with IDS is a reasonable treatment strategy, and complete debulking surgery is optimum.